Managerial ownership dynamics and firm value☆ - Fahlenbrach, Rüdiger; Stulz, René M. (Journal of Financial Economics, 2009)
From 1988 to 2003, the average change in managerial ownership is significantly negative every year for American firms. We find that managers are more likely to significantly decrease their ownership when their firms are performing well and more likely to increase their ownership when their firms become financially constrained. When controlling for past stock returns, we find that large increases in managerial ownership increase Tobin's q. This result is driven by increases in shares held by officers, while increases in shares held by directors appear unrelated to changes in firm value. There is no evidence that large decreases in ownership have an adverse impact on firm value. We rely on the dynamics of the managerial ownership/firm value relation to mitigate concerns in the literature about the endogeneity of managerial ownership.